Reduction in heart failure hospitalization rate during coronavirus disease 19 pandemic outbreak. (23rd October 2020) - Severino, Paolo; D'Amato, Andrea; Saglietto, Andrea; D'Ascenzo, Fabrizio; Marini, Claudia; Schiavone, Marco; Ghionzoli, Nicolò; Pirrotta, Filippo; Troiano, Francesca; Cannillo, Margherita; Mennuni, Marco; Rognoni, Andrea; et al.
Abstract: Aims: The recent coronavirus disease 19 (COVID‐19) pandemic outbreak forced the adoption of restraint measures, which modified the hospital admission patterns for several diseases. The aim of the study is to investigate the rate of hospital admissions for heart failure (HF) during the early days of the COVID‐19 outbreak in Italy, compared with a corresponding period during the previous year and an earlier period during the same year. Methods and results: We performed a retrospective analysis on HF admissions number at eight hospitals in Italy throughout the study period (21 February to 31 March 2020), compared with an inter‐year period (21 February to 31 March 2019) and an intra‐year period (1 January to 20 February 2020). The primary outcome was the overall rate of hospital admissions for HF. A total of 505 HF patients were included in this survey: 112 during the case period, 201 during intra‐year period, and 192 during inter‐year period. The mean admission rate during the case period was 2.80 admissions per day, significantly lower compared with intra‐year period (3.94 admissions per day; incidence rate ratio, 0.71; 95% confidence interval [CI], 0.56–0.89; P = 0.0037), or with inter‐year (4.92 admissions per day; incidence rate ratio, 0.57; 95% confidence interval, 0.45–0.72; P < 0.001). Patients admitted during study period were less frequently admitted in New York Heart Association (NYHA) Class II compared with inter‐year period ( P = 0.019). At covariance analysis NYHA class was significantly lower in patients admitted during inter‐year control period, compared with patients admitted during case period ( P = 0.014). Conclusions: Admissions for HF were significantly reduced during the lockdown due to the COVID‐19 pandemic in Italy.